Islamic Family Law and Economic Thot Framework; A Study of The Curriculum Materials of Darul Muttaqin Islamic Boarding School In Bogor - Sopiyan Sopiyan; Reksiana Reksiana; Eneng Purwanti; Siti Asiah; Ghulam M. Nukhba (Universitas Muhammadiyah Bandung, 2025)
This study examines how Islamic family law materials in the curriculum of Pesantren Darul Muttaqin Bogor contribute to the formation of santri’s economic reasoning. The article responds to the tendency to treat Islamic family law in pesantren merely as a doctrinal field concerned with marriage, inheritance, and domestic obligations, while overlooking its economic implications. Using a qualitative intrinsic case study design, the research analyses curriculum materials, especially al-Fiqh al-Wadhih, Bulugh al-Maram, and fiqh al-mawarith, supported by document analysis, semi-structured interviews, and limited participant observation. The findings show that Islamic family law is taught as a layered body of knowledge that connects legal norms, moral responsibility, and socio-economic awareness. Themes such as mahr, nafaqah, family property, bequest, and inheritance introduce santri to concepts of ownership, financial obligation, women’s economic rights, asset transfer, and distributive justice. The study also finds that the pesantren’s integrative learning environment—through classroom instruction, dormitory discipline, organisational duties, and daily habituation—enables these concepts to be internalised as practical orientations toward responsibility, productivity, and economic accountability. Theoretically, this study contributes to pesantren studies, Islamic family law, and Islamic economics by arguing that family jurisprudence can function as a hidden economic curriculum. It shows that santri’s economic consciousness may be shaped not only through entrepreneurship programs, but also through classical legal materials that frame family life as a domain of responsibility, property ethics, and distributive justice.